Maintaining Legitimacy: The Environmental Management Practices and Green Innovation on Indonesian Manufacturing Companies - Ina Indriana (Journal of Applied Business, Taxation and Economics Research, 2022)
Maintaining legitimacy through environmental management practices and green innovation is often seen as less supportive of the company's efforts to improve performance and competitive advantage. This paper aims to analyse the legitimacy motivation of companies participating in the performance rating assessment program in environmental management (PROPER). Another goal is to find out the effectiveness of the motive to maintain legitimacy in improving environmental performance and competitive advantage. The document analysis employs to analyse data. The findings indicate that maintaining the legitimacy of stakeholders is the motivation for manufacturing companies to carry out environmental management and green innovation. The data also suggest that maintaining legitimacy from a wider range of stakeholders brings more tangible economic and non-economic benefits, such as higher environmental performance and competitive advantage, compared to focusing solely on maintaining legitimacy from the government. The findings also show that the PROPER deconcentration policy which is being promoted to improve supervision of companies in environmental management by involving the provincial government, companies and universities is effective in increasing the number and compliance of companies in environmental management. However, the government needs to look for breakthroughs so that companies apply environmental practices beyond compliance by considering several points from the criteria or requirements for exceeding compliance in article 6, such as the implementation of environmental management systems, achieving energy efficiency, saving water, reducing and utilizing waste. non-hazardous materials and solid waste, are transferred to the criteria or compliance requirements in article 5.